Problematizing the neurochemical subject of anti-depressant treatment: The limits of biomedical responses to women's emotional distress - Fullagar, Simone; O'Brien, Wendy (Health (London, England : 1997), 2013)
In this article we situate empirical research into women's problematic experiences of anti-depressant medication within broader debates about pharmaceuticalization and the rise of the neurochemical self. We explore how women interpreted and problematized anti-depressant medication as it impeded their recovery in a number of ways. Drawing upon Foucauldian and feminist work we conceptualize anti-depressants as biotechnologies of the self that shaped how women thought about and acted upon their embodied (and hence gendered) subjectivities. Through the interplay of biochemical, emotional and socio-cultural effects medication worked to shape women's self-in-recovery in ways that both reinscribed and undermined a neurochemical construction of depression. Our analysis outlines two key discursive constructions that focused on women's problematization of the neurochemical self in response to the side-effects of anti-depressant use. We identified how the failure of medication to alleviate depression contributed to women's reinterpretation of recovery as a process of 'working' on the emotional self. We argue that women's stories act as a form of subjugated knowledge about the material and discursive forces shaping depression and recovery. These findings offer a gendered critique of scientific and market orientated rationalities underpinning neurochemical recovery that obscure the embodied relations of affect and the social conditions that enable the self to change.